On the Realization of TractsTool - Burgueño-Caballero, Lola; Wimmer, Manuel; Troya-Castilla, Javier; Vallecillo-Moreno, Antonio Jesús (My University, 2013)
Model transformations play an important role in Model-Driven Engineering (MDE), and as their size and complexity grow, there is an increasing need to count on tool support for testing their correctness. In this presentation, we introduce TractsTool, a tool for specifying and testing several different kinds of model transformations, e.g., model-to-model, model-to-text, and text-to-model transformations, based on contracts. We explain the main principles behind the tool, demonstrate some of its capabilities by a running example, and show how it is internally realized by using MDE techniques. In particular, we describe the transformation chain that is used to compute the test results. TractsTool with accompanying information is available at: http://atenea.lcc.uma.es/index.php/Main_Page/Resources/Tracts
Keywords: Ingeniería del software; Software Engineering; Model-driven development